2014
DOI: 10.1073/pnas.1411925111
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of a signal that synchronizes cell movements in swarms of Myxococcus xanthus

Abstract: We offer evidence for a signal that synchronizes the behavior of hundreds of Myxococcus xanthus cells in a growing swarm. Swarms are driven to expand by the periodic reversing of direction by members. By using time-lapse photomicroscopy, two organized multicellular elements of the swarm were analyzed: single-layered, rectangular rafts and round, multilayered mounds. Rafts of hundreds of cells with their long axes aligned in parallel enlarge as individual cells from the neighborhood join them from either side. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
(45 reference statements)
2
22
0
Order By: Relevance
“…We hypothesize that the introduction of nonmotile cells within a motile population breaks the harmony of the population and leads to swarm dysfunction. Consistent with this view, Kaiser and Warrick have recently demonstrated that the movement of cells within a swarm shows a surprisingly high degree of synchronization (37). We suggest that this synchronization is disrupted when nonmotile cells are mixed in the population.…”
Section: Discussionsupporting
confidence: 83%
“…We hypothesize that the introduction of nonmotile cells within a motile population breaks the harmony of the population and leads to swarm dysfunction. Consistent with this view, Kaiser and Warrick have recently demonstrated that the movement of cells within a swarm shows a surprisingly high degree of synchronization (37). We suggest that this synchronization is disrupted when nonmotile cells are mixed in the population.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, consider the delta-proteobacterium M. xanthus , a social predator that inhabits soil, arguably one of the most complex ecosystems on the planet. Potentially the primate of the eubacteria, M. xanthus is renowned for its myriad collective behaviors, including structured, multidimensional swarming motility ( Kaiser and Warrick, 2014 ), pack-like predation ( Berleman and Kirby, 2009 ), and the use of chemical cues to lure faster-moving prey ( Shi and Zusman, 1993 ), as well as a complex developmental sequence leading to fruiting body formation and sporulation. At 9.14 Mbp, the M. xanthus genome is one of the top 20 in size and expresses 687 ST systems, of which more than half (54%, N = 372) are 2CSs.…”
Section: Part 2 the Bacterial Cognitive Toolkitmentioning
confidence: 99%
“…Nevertheless, a stream of recent research into swarming motility in M. xanthus ( Mignot et al, 2005 , 2007 ; Nudleman et al, 2005 ; Mauriello et al, 2009b ; Nan et al, 2010 ; Kaiser and Warrick, 2011 , 2014 ; Pathak et al, 2012 ) has thrown light on very different processes of motility that involve vastly more components and produce much more observable behavior than flagellar rotation mediated by Che proteins.…”
Section: Part 2 the Bacterial Cognitive Toolkitmentioning
confidence: 99%
See 1 more Smart Citation
“…FrzCD protein clusters transiently realign between adjacent cells upon side-by-side contact to trigger cell reversals [38]. These interactions between side-by-side cells may help the population to coordinate and synchronize cell movements [39]. Thus, M. xanthus uses a variety of cell-cell interactions to organize the macro-scale movement of the swarm unit.…”
Section: Introductionmentioning
confidence: 99%